2014
DOI: 10.1111/jphd.12056
|View full text |Cite
|
Sign up to set email alerts
|

Overview and quality assurance for the oral health component of the National Health and Nutrition Examination Survey (NHANES), 2009‐2010

Abstract: Overall, the data reliability analyses conducted for 2009-2010 indicate an acceptable level of data quality and that examiner (dental hygienist) performance in this data collection cycle is similar to prior survey periods since the NHANES continuous survey began in 1999.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
77
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(83 citation statements)
references
References 15 publications
5
77
1
Order By: Relevance
“…4 and 20.8 [O'Mullane, 1996]. Caries experience in Jerusalem was lower than in the USA, Canada, France and Denmark [Hescot et al, 1997;Brodeur et al, 2000;Dye Krustrup and Petersen, 2007], and similar to figures reported in Australia . In relation to Mediterranean countries, caries experience in Jerusalem was lower than in Lebanon, Syria and Turkey [Doughan et al, 2000;Beiruti et al, 2001;Namal et al, 2008], but higher than in Jordan and Egypt [World Health Organization, 2010].…”
Section: Discussionsupporting
confidence: 52%
“…4 and 20.8 [O'Mullane, 1996]. Caries experience in Jerusalem was lower than in the USA, Canada, France and Denmark [Hescot et al, 1997;Brodeur et al, 2000;Dye Krustrup and Petersen, 2007], and similar to figures reported in Australia . In relation to Mediterranean countries, caries experience in Jerusalem was lower than in Lebanon, Syria and Turkey [Doughan et al, 2000;Beiruti et al, 2001;Namal et al, 2008], but higher than in Jordan and Egypt [World Health Organization, 2010].…”
Section: Discussionsupporting
confidence: 52%
“…32 The national trainer and reference examiner for the NHANES (Dr. Bruce Dye) supervised the training and Quality Assurance (QA) using procedures described previously. 32 A local dental epidemiologist, trained and calibrated by the NHANES reference examiner to perform repeat examinations on the study participants, served as the local reference examiner and provided ongoing monitoring of the three dental examiners, evaluating their assessments and providing remediation when necessary. Approximately 9% of the 571 enrolled participants received a repeat dental caries and periodontal examination conducted by the reference examiner.…”
Section: Methodsmentioning
confidence: 99%
“…Clinical attachment level was calculated as the difference between PD and GR. Reliability analyses conducted on the periodontal data collected over the 2009–2010 interval indicated acceptable levels of agreement and quality . Information regarding the reliability of the data collected from 2011–2012 is currently unavailable …”
Section: Methodsmentioning
confidence: 95%